Kebijakan Developmental State Indonesia dalam Perdagangan Komoditas Hortikultura, Hewan, dan Produk Hewan - Nur Yekti, Septian (Indonesian Perspective, 2017)
Indonesia insists to defend its regulation on trade of horticulture, animals, and animal products after its loss on New Zaeland’s indictment in Dispute Settlement Body (DSB) of World Trade Organization (WTO). Indonesia appealed the DSB decision, despite previous findings in DSB panel which reports that Indonesia’s regulations contains trade restriction and various trade barriers. This paper analyzes the reason why Indonesia appealed the DSB Panel decision, despite the fact that Indonesia violates WTO principles which lead to free trade barriers. This paper uses law perspective to find out whether Indonesia really violates the law or not. Besides, this paper also uses developmental state theory to analyze the case. The theory takes root in the merchantilism which emphasizes on export, domestic production, and national welfare. Developmental state’s position lies between liberalization and centered-plan policy which means that the country that applying this policy joins the globalization and plays its role in international order to reach national welfare.Keywords: developmental state, trade dispute settlement, trade restriction